'Interconnectedness with Nature': The Imperative for an African-centered Eco-philosophy in Forest Resource Conservation in Nigeria. Issue 1 (2nd January 2022) - Okpoko, Mercy Osemudiame
ABSTRACT: Calls for society to reconnect with nature are commonplace in environmental discourse. The expression 'Interconnectedness with Nature' has a place in African eco-philosophy. The departure from this African eco-philosophy may be a potential contributor to present rate of forest depletion in Nigeria. By employing the African eco-philosophy of 'interconnectedness with nature', this study considers its capacity to demonstrate the relevance of African socio-ecological ethics for forest conservation. There is need for such values to form the theoretical foundation of environmental policies and actions in Nigeria to achieve the required value change for more commitment to forest resource conservation within Nigeria.